Ephemeral landform development following rapid coastal uplift in the southern orogen of Taiwan. Issue 12 (22nd July 2021) - Giletycz, Slawomir Jack; Lin, Andrew Tien‐Shun; Yamada, Katsura; Wang, Liang‐Chi; Chien, Chih‐Wei; Lou, Jiann‐Yuh; Huang, Neng‐Wei; Ting, Che‐Yung; Shih, Kuo‐Wei
Abstract: Newly emerged landscapes above sea level are characterized by rapidly evolving geomorphic systems where the initial fluvial pattern adapts to a former submarine topography. Such an early formed fluvial system establishes drainage basins and unstable landforms that characterize high topographic asymmetry which are prone to fast removal or reorganization. Transitional landscapes might form depositional systems as lakes or ponds that subsequently are incised, captured and incorporated into drainage basins. In this study we focus on the recently emerged Hengchun Peninsula to survey its paleoenvironment evolution. Three drillings performed in the Gangkou basin with fieldwork revealed several indicators that reconstructed stages of the landscape reorganization. The major finding shows an ephemeral large lake in the central part of the Hengchun Peninsula that was drained to the Pacific c . 6000 bp . The lake belonged to an ephemeral lakeland that was created after the emergence of the peninsula. Currently, several areas as relict landforms indicate this stage of topography evolution that through high rates of incision and subsequent captures, transforms into drainage basins. Furthermore, two drillings show brackish waters at the present estuary of the Gangkou basin. These two different paleoenvironments today build one system – Gangkou catchment. Long‐term uplift rates show that a hanging wall of the Hengchun Fault plays a significant role in the creation of a lakeland by tilting the peninsula's surface. The tilt impacts on asymmetrical emergence of the peninsula and catchment development. Our study shows that a new geomorphic system might create depositional ephemeral landforms (lakes) that represent phases of early topography evolution after emergence above a sea level that are subjected to instantaneous rearrangement and evolves through large‐scale phases before it reaches a topographic steady‐state. Abstract : Three‐dimensional image of southern Hengchun Peninsula and a former ephemeral Manzhou Lake in the present Gangkou basin.